Acquired factor VIII inhibitor and subsequent development of non-Hodgkin's lymphoma: a case report and review of the literature. Issue 8 (December 2015) - Porru, Mariagrazia; Mameli, Antonella; Cianchetti, Elisabetta M.; Musu, Mario; Montisci, Roberto; Finco, Gabriele; Marongiu, Francesco
Abstract : Acquired hemophilia A (AHA) is a rare disorder caused by the development of factor VIII autoantibodies. It can induce acute and major hemorrhages in patients with negative personal and family history of bleeding. AHA is frequently associated with hematologic malignancies. This study describes the first case of AHA in a patient who developed a mantle cell lymphoma after a year and half of complete remission. It also provides an example of an initial wrong approach in terms of diagnosis and treatment, as well as of a very long course of the disease. Further, a review of AHA-associated lymphomas from 1974 to 2014 is also presented. Clinical and laboratory staff should be alert to the possibility of such an event when the medical history of patients is enriched with new symptoms or signs. A follow-up of at least 2 years might therefore be required.